Time to hold last rites for martial-rape immunity - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2017)
When Minister for Social and Family Development Tan Chuan-Jin said earlier this month in Parliament that the Government was “actively reviewing” a husband’s limited immunity from marital rape, he asserted that a married woman should have equal protection against sexual violence as an unmarried woman.